Nonbiological Predictors of Sexual Desire in Women with Female Sexual Interest and Arousal Disorder - Pouran Akhavan-Akbari; Gity Ozgoli; Masoumeh Simbar; Mohammad Ali Besharat (مجله دانشکده پزشکی اصفهان, 2018)
Background: Female sexual interest and arousal disorder (FSIAD) is one of the most prevalent sexual problems among women, and is a multifactorial dysfunction. The purpose of this study was to examine nonbiological predictors of sexual desire in women with female sexual interest and arousal disorder.